2012
DOI: 10.1186/1472-6963-12-134
|View full text |Cite
|
Sign up to set email alerts
|

Brain Gains: a literature review of medical missions to low and middle-income countries

Abstract: BackgroundHealthcare professionals’ participation in short-term medical missions to low and middle income countries (LMIC) to provide healthcare has become common over the past 50 years yet little is known about the quantity and quality of these missions. The aim of this study was to review medical mission publications over 25 years to better understand missions and their potential impact on health systems in LMICs.MethodsA literature review was conducted by searching Medline for articles published from 1985–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
219
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(229 citation statements)
references
References 29 publications
3
219
0
7
Order By: Relevance
“…Para subsanar este problema se organizan equipos de personal de salud para resolver casos seleccionados, por lo general patologías quirúrgicas, que no pueden ser resueltos por el sistema local 5,13,14 . Este tipo de misiones tienen las ventajas de la optimización del trabajo, porque se trata de equipos compenetrados (aunque muchos pueden no conocerse con anticipación), la posibilidad de resolver patologías complejas e intentar asegurar un nivel de atención estándar a los pacientes.…”
Section: Caracterización De La CIunclassified
See 3 more Smart Citations
“…Para subsanar este problema se organizan equipos de personal de salud para resolver casos seleccionados, por lo general patologías quirúrgicas, que no pueden ser resueltos por el sistema local 5,13,14 . Este tipo de misiones tienen las ventajas de la optimización del trabajo, porque se trata de equipos compenetrados (aunque muchos pueden no conocerse con anticipación), la posibilidad de resolver patologías complejas e intentar asegurar un nivel de atención estándar a los pacientes.…”
Section: Caracterización De La CIunclassified
“…Martiniuk et al 14 realizaron una revisión sistemática de la literatura evaluando los OM. En esta refieren que los países que más OM envían son Estados Unidos de Norteamérica, Canadá, Reino Unido y Australia, siendo las regiones beneficiadas de este apoyo, principalmente, África, América Central y Asia.…”
Section: Caracterización De La CIunclassified
See 2 more Smart Citations
“…The authors' review revealed the paucity of literature providing quantitative data on costs, quality, regulation, and outcome. 5 More recently, Sykes reviewed articles about MSTs in an effort to evaluate specific indicators, including treatment interventions, cost effectiveness, quality assessment, factors limiting MSTs from performing evaluations, reasons healthcare providers participate, role of education, and how those affected by MSTs perceive the visiting teams and their activities. Most of the author's questions were left unanswered, so he concluded that ''reporting has dealt largely with outputs rather than outcomes''.…”
mentioning
confidence: 99%